73.5k views
1 vote
7 + y/2= -3. This is two step equation

7 + y/2= -3. This is two step equation-example-1
User Moonfly
by
5.9k points

2 Answers

2 votes
First subtract 7 from both side
7+y/2=-3
-7. -7
And them multiple de two from both side
2.y/2=-10.2
And the answer is 20
User Jolyn
by
6.2k points
5 votes

Answer:

y = -20

Explanation:

7 +
(y)/(2) = -3

The first step is to isolate the variable by subtracting 7 from both sides:


(y)/(2) = -10

Then, to get rid of the *divided by 2*, multiply both sides by 2:

y = -20

User YanivGK
by
5.6k points